In-situ oxidation, addition and cyclization reaction of 5, 6-diamino-1, 10-phenanthroline to construct copper(I)-diimine–diphosphine complexes. (28th May 2015) - Yao, Xi-Xi; Guo, Ya-Meng; Liu, Rong; Feng, Xiao-Yan; Li, Hao-Huai; Liu, Nian; Yang, Feng-Lei; Li, Xiu-Ling
Graphical abstract: Reaction of 5, 6-diamino-1, 10-phenanthroline (dap), two chelating diphosphine ligands (PP) with [Cu(MeCN)4 ]ClO4 afforded three types of Cu(I)-diimine–diphosphine complexes, [Cu(dap)(PP)]ClO4, [Cu2 ( μ -pdi)(PP)2 ](ClO4 )2 and [Cu2 ( μ -ttpd)(xantphos)2 ](ClO4 )2, where dap was suggested to undergo in-situ oxidation, addition and cyclization reaction induced by Cu(I) complexes. Abstract: Reaction of 5, 6-diamino-1, 10-phenanthroline (dap), chelating diphosphine ligands, 9, 9-dimethyl-4, 5-bis(diphenylphosphino)-9H-xanthene (xantphos) and bis[(2-diphenylphosphino)phenyl] ether (POP) with [Cu(MeCN)4 ]ClO4 afforded mononuclear [Cu(dap)(PP)]ClO4 (PP = xantphos, 1a ; POP, 2a ), binuclear [Cu2 ( μ -pdi)(PP)2 ](ClO4 )2 (pdi = 1, 10-phenanthroline-5, 6-diimine) (PP = xantphos, 1b ; POP, 2b ) and [Cu2 ( μ -ttpd)(xantphos)2 ](ClO4 )2 (1c ) (ttpd = 8b, 9, 18, 18a-tetrahydrotetrapyrido[3, 2-a:2′, 3′-c:3″, 2″-h:2‴, 3‴-j]phenazine-8b, 18a-diamine) complexes. The ligand pdi with a quinone diimine form in complexes1b and2b is suggested to result from an in-situ two-electron oxidation of dap under the catalysis of Cu(I) and is stabilized by the coordination to Cu(I) ion, while the unprecedented ligand ttpd in complex1c is suggested to originate from the in-situ oxidation, addition and cyclization reaction of dap induced and stabilized by crystallized Cu(I)-diimine–diphosphine complex. The plausible formation mechanisms for the Cu(I) complexes are proposed.